Whitehall, Port-of-Spain, Trinidad - Norton, Noel, P. (Ace Printery, Trinidad, 2010)
The postcard shows Whitehall, one of the landmarks around the Queen’s Park Savannah. It has been used as the official office of the Prime Minister of Trinidad and Tobago. The structure was originally built at the turn of the 20th century by a wealthy cocoa planter Leon Agostini and called Rosenweg (Way of the Roses).
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Historical buildings; Port of Spain; Public buildings